Konsep-Konsep Al-Qur’an Dalam Penanggulangan Patologi Sosial - Hamidullah Mahmud (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2020)
Humans as one of the creations of Allah SWT, always need the intervention of the Creator to solve all problems. This paper reviews the importance of making religious values ​​(al-Qur'an) a source of solving social problems. This is based on the fact that the Qur'an has discussed several types of social ills, such as: sexual perversion, gambling, alcoholism, theft, corruption, crime and so on. In addition to having told various types of social ills or known in terms of social science as social pathology, the Qur'an also explains the causes of their emergence, as well as laying strong foundations so that humans can get out of these problems by reinforcing values monotheism, noble character, uphold justice, responsibility and glue the sensitivity of brotherhood values. The method used in this paper is qualitative with the interpretation method maudhū'i.